The Decision Of Micro And Small Industries To Implement Certification And The Impact On Industrial Performance - Irwandi, Putra; Feryanto, Feryanto; Fariyanti, Anna (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The importance of certification is expected to ensure quality, quality, and relevant standards. This study aims to analyze the factors that influence micro and small industries in the food and beverage sector in Indonesia to implement certification and its impact on industry performance. There are 12 factors that influence the industry to apply certification including company age, business entity status, business place status, owner's education level, owner's age, export activity, training activities, joining business associations, assistance from the government, access to credit, capital, and research and development which are analyzed using binary logistic analysis. Meanwhile, the analysis of the impact of certification on performance using a propensity score matching approach includes turnover, profit, and number of workers. This data is sourced from the Central Statistics Agency's 2019 micro and small industry survey with a total of 1,837 micro and small industries in the food and beverage sector that have certification and a group that does not have certification totaling 23,350 industries. Data processing using STATA17 software and microsft excel. Based on the results of the study, there are 9 variables that affect and are significant to the application of certification, while 3 other variables namely export activity variables, capital, and research and development variables have no significant effect. The results of the impact analysis show that certification has no effect on increasing business turnover. While the impact of certification on profit and labor has a positive effect up to Rp7.5 million for industries that have certification.